Oncology Providers’ Perspectives on Psychedelic-Assisted Therapy - Krishna S. Hanubal; Akul N. Munjal; Jino Park; Rufus Banks; Esther Choi; Michael A. Hoyt; Jessica N. Humphreys; Mona Mojtahedzadeh; Jeremy P. Harris (American Journal of Hospice and Palliative Medicine®, 2026)
Purpose Despite most psychedelic substances remaining Schedule I, clinical research exploring psychedelic-assisted therapy (PAT) in oncology is expanding. We sought to assess oncology providers’ attitudes toward and understanding of PAT. Methods We conducted a cross-sectional survey of healthcare professionals involved in oncology across five academic institutions in California, South Carolina, and Florida, and one nonacademic institution in Georgia. The survey was also distributed to 4500 members of the American Academy of Hospice and Palliative Medicine. Items assessed demographics, familiarity and concerns regarding psychedelic medications, and willingness to recommend PAT based on case-based scenarios. Results Of 5084 surveyed, 385 responded (8% response rate). Most respondents (85%) were palliative care physicians. Only 44% were familiar with the legal and regulatory status of psychedelic agents. While 49% had received patient inquiries about PAT, 80% did not feel comfortable counseling patients on its use. Primary concerns included unknown drug interactions with cancer therapies and safety in the setting of oncologic comorbidities. Factors encouraging future PAT adoption included increased education and access to experienced treatment centers. On multivariate analysis, willingness to recommend PAT was associated with familiarity with emerging PAT data, knowledge of the legal and regulatory status of psychedelics, and prior patient inquiry about PAT. Provider age, specialty, and other clinicodemographic factors were not significant predictors. Conclusion Many oncology providers report patient interest in PAT but lack confidence to counsel them. Findings underscore the need for targeted provider education and further clinical research to support informed decision-making about PAT in oncology.